2005
DOI: 10.1128/jb.187.8.2858-2869.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Structural Analysis of the Bacteroides Conjugative Transposon CTn341

Abstract: The genetic structure and functional organization of a Bacteroides conjugative transposon (CTn), CTn341, were determined. CTn341 was originally isolated from a tetracycline-resistant clinical isolate of Bacteroides vulgatus. The element was 51,993 bp long, which included a 5-bp coupling sequence that linked the transposon ends in the circular form. There were 46 genes, and the corresponding gene products fell into three major functional groups: DNA metabolism, regulation and antibiotic resistance, and conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 48 publications
0
38
0
1
Order By: Relevance
“…Genes encoding VirB4-like and VirD4-like components associated with T4SSs were identified in 13 of the genomes, but other components typically associated with T4SSs were absent. Several of the T4SS genes were associated with known conjugative transposons (62,63), and the others may also be involved in conjugative transfer of DNA. Genes associated with possible T1SSs, T5SSs, and T8SSs were detected in a few species, whereas T6SSs, T7SSs, and chaperone-usher pathway genes were not detected in any.…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding VirB4-like and VirD4-like components associated with T4SSs were identified in 13 of the genomes, but other components typically associated with T4SSs were absent. Several of the T4SS genes were associated with known conjugative transposons (62,63), and the others may also be involved in conjugative transfer of DNA. Genes associated with possible T1SSs, T5SSs, and T8SSs were detected in a few species, whereas T6SSs, T7SSs, and chaperone-usher pathway genes were not detected in any.…”
Section: Resultsmentioning
confidence: 99%
“…The regulation pathway involves a repressor related to phage lambda cI repressor. It could also involve a putative regulator related to another type of phage repressors, the "cI-like" repressors.Whereas in silico analyses revealed that numerous genomic islands could be integrative and conjugative elements (ICEs) or elements derived from ICEs (2,4,9,13,15,19,25,26), only a few ICEs have been described. ICEs excise by site-specific recombination, transfer through conjugation, and integrate into a replicon of the recipient cell (8).…”
mentioning
confidence: 99%
“…Analysis of the genome sequence of strain W83 (9,26) reveals one potential mediator of horizontal DNA transfer by conjugation, a distant homolog of type IV secretion systems found in other gram-negative bacteria (8). The 12-kb region encodes proteins most similar to those encoded by the DNA transfer regions (tra genes) of the Bacteroides conjugative transposons cTnDot and cTn341 (30% to 75% identity) (3,5).…”
mentioning
confidence: 99%